THE CONCEPT OF SMART TOURISM MANAGEMENT IN THE FRAMEWORK OF IMPLEMENTING SUSTAINABLE DEVELOPMENT STRATEGIES FOR TERRITORIAL COMMUNITIES - Tymoshenko, Тetiana (Public Administration and Regional Development, 2021)
In the article, the author has formulated proposals for the implementation of mechanisms for public tourism management at the regional and local levels in Ukraine, taking into account the latest innovations in the framework of the decentralization reform and modern global trends. In the context of the subject of the research, the content essence of the three-tier tourism management system is revealed, taking into account the amendments to the Law "On the Foundations of State Regional Policy" adopted by the Verkhovna Rada of Ukraine on June 1, 2021 in the first reading, which introduce a three-tier system of strategic planning: state - region - society. The understanding of the term and the application of the concept of SMART TOURIST DESTINATION (reasonable management of a tourist destination), approved by the provisions of the State Strategy for Regional Development for 2021-2027, is indicated. The need for the development of a cascade planning system for the development of tourist destinations, taking into account the provisions of strategic documents and developed regulatory legal acts of the highest level of management and the possibilities of the mechanism of cooperation of territorial communities, has been determined. The article describes the regulatory framework as an element of a complex regulatory mechanism for quality control of the implementation of an integrated management system for a tourist destination, taking into account the best world practices. It is proposed: to develop an effective and comprehensive mechanism for the implementation of a tourist destination management system in the regions of Ukraine and control over the quality of the provision of tourist services based on the concept of SMART TOURISM DESTINATION. Identified promising areas for further theoretical and practical research to improve the regulatory mechanism for monitoring the quality of tourist services in modern Ukraine, including with the participation of local governments on the territory of newly territorial communities to intensify the process of developing and approving guidelines and a package of draft regulatory legal acts in order to organize the process of debugging the tourist destination management system at the regional and local levels.